Pengaruh Indeks Pembangunan Manusia, Laju Pertumbuhan Penduduk, dan Inflansi terhadap Tingkat Kemiskinan Jawa Barat 2020-2022 - Vikcy Rananda; Nira Salma Muliasari; Meita Noveliza; Nova Ayu Wulandari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Poverty is an unresolved problem in Indonesia. When a person or family is unable to meet their basic needs, it is called poverty. This research aims to determine whether there is a relationship between the variables Human Development Index (HDI) (X1), Population Growth Rate (X2), Inflation (X3) and West Java Poverty Level 2020–2022 (Y). This study uses annual data from 2019–2022. To carry out this analysis, quantitative methods are used: coefficient of determination, classical assumption test, autocorrelation test, multiple linear regression analysis, t test (partial test), and F test (simultaneous test). All of this was done using the SPSS 25 program. The analysis results show that population growth rate, inflation and the Human Development Index (HDI) influence poverty levels simultaneously or separately.